Efek Toksisitas Subletal Insektisida Organoklorin Endosulfan Terhadap Tingkat Konsumsi Oksigen dan Histopatologi Insang Benih Ikan Nila (Oreochromis niloticus) - Adista Fadilah; Boedi Setya Rahardja (Journal of Aquaculture Science, 2023)
The uncontrolled use of organochlorine insecticides in the agricultural sector has an impact on water pollution and threatens the lives of organisms in it. Pollutants can reduce water quality and interfere with the performance of fish organ systems, triggering stress and even death. The purpose of the study was to determine the sublethal effects of the organochlorine insecticide endosulfan on the level of oxygen consumption and histopathology of tilapia seed gills. The research was conducted at the Faculty of Fisheries and Marine Science, Universitas Airlangga, from March to May 2021. This study used a completely randomized design (CRD) experimental method. The treatment used was exposure to organochlorine endosulfan doses of 10%, 30%, 50%, and 70% with LC50-96 hours, which was observed for 28 days. Oxygen consumption data were analyzed by Analysis of Variance, followed by DMRT (Duncan's Multiple Range Test). While gill histopathology data were analyzed descriptively by comparing normal and abnormal gill histopathology. The results showed that the sublethal toxicity of the organochlorine insecticide endosulfan had a significant effect (p<0.05) on the level of oxygen consumption and had an impact on the histopathological condition of the tilapia seed gills. The types of gill damage found were oedema, hyperplasia, lamellar fusion, hemorrhage, and necrosis.